New Evidence on the Cyclicality of Fiscal Policy - Carneiro, Francisco G.; Garrido, Leonardo (World Bank, Washington, DC, 2015)
This paper presents new evidence on the patterns of cyclicality in the fiscal policy stance of developing and industrialized countries over a period of more than three decades covering 180 countries during 1980–2012. First, the paper considers issues of robustness in the choice of the proxy for fiscal cyclicality by using alternative filtering methods to check whether this influences the results and leads to any differences in a country’s reported within-period average, and across-period changes in fiscal stance. Second, a country-specific approach is used to split the sample into sub-periods based on a test for structural break in the series of real gross domestic product per capita. Third, the paper investigates the extent to which countries behave pro-cyclically or counter-cyclically in different phases of the business cycle. In line with earlier findings in the literature, the analysis confirms that there is a causal link running from stronger institutions to less pro-cyclical fiscal policy, even after controlling for the endogeneity of institutions and other determinants of fiscal policy.